2005
DOI: 10.1021/om050343b
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Platinum-Based Triplet Emitter for OLED Applications

Abstract: The synthesis of a novel trifunctional Pt(II) cyclometalated complex in which the hole-transporting (HT), electron-transporting (ET), and electroluminescent (EL) components are integrated into a single molecule is accomplished, and this complex can be sublimed and used for the fabrication of neat emissive layer electrophosphorescent devices.# Dedicated to Prof. F. Albert Cotton on the occasion of his 75th birthday.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(80 citation statements)
references
References 36 publications
4
76
0
Order By: Relevance
“…[15,16,19,32,33,41,43,[47][48][49][50][51][52][53] The mono-, di-and trinuclear (RC^N^N) complexes of platinum(II) reported in this work are strongly emissive and have high emission quantum yields in solutions at room temperature. The emission quantum yield of 1 d (0.68 in CH 2 Cl 2 ) is significantly higher than that of [(C^N^N)PtCl] [13] and [PtA C H T U N G T R E N N U N G (tBu 2 N 2 O 2 )], [32] with the latter two showing emission at 565 (F = 0.025) and 595 nm (F = 0.12), respectively, in CH 2 Cl 2 solutions ( Table 8 II complexes: 1) the extended p-conjugation would increase the electronic delocalization, hence a smaller bond displacement change in the excited state compared to those for (C^N^N) analogues is expected.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16,19,32,33,41,43,[47][48][49][50][51][52][53] The mono-, di-and trinuclear (RC^N^N) complexes of platinum(II) reported in this work are strongly emissive and have high emission quantum yields in solutions at room temperature. The emission quantum yield of 1 d (0.68 in CH 2 Cl 2 ) is significantly higher than that of [(C^N^N)PtCl] [13] and [PtA C H T U N G T R E N N U N G (tBu 2 N 2 O 2 )], [32] with the latter two showing emission at 565 (F = 0.025) and 595 nm (F = 0.12), respectively, in CH 2 Cl 2 solutions ( Table 8 II complexes: 1) the extended p-conjugation would increase the electronic delocalization, hence a smaller bond displacement change in the excited state compared to those for (C^N^N) analogues is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we chose units that may be easily derivatized, thereby giving great flexibility to this design strategy. Wong et al [8] and Gong et al [9] have synthesized integrated molecules containing all three functionalities and shown that they are effective as a single chargetransport and emitting layer in OLEDs. Trifunctional polymers have also been prepared.…”
Section: Dedicated To Professor John J Mcgarveymentioning
confidence: 99%
“…[8,10,19] Platinum(II) complexes have been used as phosphorescent emitters in small-molecule OLEDs. [4,12,[20][21][22][23][24][25] Since the first phosphorescent OLED was reported with 2, 3,7,8,12,13,17,18-octaethyl-21H,23H-porphine platinum(II) (PtOEP) as a red emissive dopant, [4] platinum(II) complexes have been used to prepare OLEDs that give green, red, and even white EL with external quantum efficiencies as high as 16.5 %. [15] However, to date no blue OLEDs with high efficiency using platinum-complex emitters have been reported, which may be due to the fact that luminescence from platinum(II) complexes show significant spectral shifts upon dopant aggregation, leading to broad, red-shifted emission.…”
Section: Introductionmentioning
confidence: 99%